Nesting of the sparrows "Passer spp." in the white stork "Ciconia ciconia" nests in a stork colony in Kłopot (w Poland) - Bocheński, Marcin (Zielona Góra: University of Zielona Góra, Institute of Biotechnology & Environmental)
Nesting of the sparrows "Passer spp." in the White Stork "Ciconia ciconia" nests is a well known phenomenon, but there are not many papers about that. Usually, there are only short notes in monographic or popular articles or books, both about storks (e.g. Strojny 1983, Jakubiec, Szymoński 2000) and sparrows (e.g. Nankinov 1984, Cramp, Perrins 1994).
Keywords: wróblowe; ornitologia